Whipscars and tattoos The last of the Mohicans, Moby-Dick, and the Maori - Sanborn, Geoffrey (New York ; Oxford : Oxford University Press, 2011)
Through careful historical research, Geoffrey Sanborn reveals how both James Fenimore Cooper and Herman Melville relied heavily on contemporary accounts of the indigenous natives of New Zealand, the Maori, to develop the iconic characters they created in The Last of the Mohicans and Moby-Dick.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Cooper, James Fenimore, -- 1789-1851. -- Sources; Cooper, James Fenimore, -- 1789-1851 -- Characters -- Magua; Cooper, James Fenimore, -- 1789-1851 -- Knowledge -- New Zealand; Melville, Herman, -- 1819-1891. -- Sources; Melville, Herman, -- 1819-1891 -- Characters -- Queequeg; Melville, Herman, -- 1819-1891 -- Knowledge -- New Zealand; Maori (New Zealand people) in literature